Physiological and Growth Responses of Cultured Fish to Chronic Fluoride Exposure under Controlled Aquaculture Conditions - Rajesh Verma; Kiran Bala (American Journal of Biodiversity, 2024)
Aquaculture productivity and sustainability are increasingly challenged by declining water quality, particularly in regions affected by fluoride contamination. Fluoride enters aquatic environments through natural geochemical processes and anthropogenic activities, and its chronic presence in aquaculture water sources poses potential risks to cultured fish. The present study investigated the effects of prolonged fluoride exposure on growth performance, survival, and physiological health of a commonly cultured freshwater fish, Labeo rohita, under controlled laboratory conditions. Healthy fingerlings were exposed to three sub-lethal fluoride concentrations, along with a fluoride-free control, for a period of 60 days following a completely randomized experimental design. Growth parameters, including weight gain, specific growth rate, feed conversion ratio, and survival percentage, were assessed, along with behavioral and physiological indicators of stress. Water quality parameters were maintained within optimal ranges, and fluoride concentrations were regularly monitored to ensure exposure consistency. Statistical analyses were performed using one-way analysis of variance to evaluate treatment effects. The results revealed a clear concentration-dependent decline in survival, growth performance, and physiological condition of fluoride-exposed fish. Significant reductions in weight gain and specific growth rate were observed in all fluoride-treated groups compared to the control, accompanied by elevated feed conversion ratios, indicating impaired feed utilization efficiency. Behavioral alterations such as reduced feeding activity, sluggish movement, and loss of equilibrium were evident at higher fluoride concentrations. The body condition factor declined progressively with increasing fluoride exposure, reflecting compromised health status. The findings demonstrate that chronic fluoride exposure, even at sub-lethal concentrations, can exert substantial negative impacts on fish health and aquaculture productivity. These results highlight the importance of regular monitoring of fluoride levels in aquaculture water sources and the implementation of effective mitigation strategies. Ensuring fluoride-safe water is essential for sustainable aquaculture development, fish welfare, and long-term economic viability in fluoride-affected regions.